Cultural and clinical challenges in sexual health care provision to men who have sex with men in Tanzania: a qualitative study of health professionals' experiences and health students' perspectives - Lucy R. Mgopa; B. R. Simon Rosser; Michael W. Ross; Gift Gadiel Lukumay; Inari Mohammed; Agnes F. Massae; Sebalda Leshabari; Ever Mkonyi; Stella Emmanuel Mushy; Dorkasi L. Mwakawanga; Maria Trent; James Wadley; et al. (BMC, 2021)
Abstract Background Health care providers across sub-Saharan Africa continue to face challenges while delivering sexual health care services. We explored the experiences, views and challenges of health care professionals and health students across different disciplines in Tanzania, towards delivery of sexual health services to men who have sex with men. Methods Utilizing a qualitative approach, we recruited 121 health care professionals (providers) and students from the fields of midwifery, nursing and medicine in Dar es Salaam, Tanzania. We conducted 18 focus groups discussions, stratified by profession and experience, to investigate clinical management and challenges while addressing a case of an adult male presenting with rectal gonorrhea. Results Findings indicated this case as extremely sensitive, clinical management involved establishing rapport and consent, medical care from history taking to treatment, and referral to other specialties. However, the illegal status of homosexuality in Tanzania was a primary concern to participants, this triggered the clinical care of this case scenario as challenging. There were uncertainties whether or not that such a case should be reported to the authorities. Conclusion Findings from this study revealed a need for training health students in Tanzania to address sexual health issues including accurate information on homosexuality, reporting requirements and clinical management in the legal and socio-cultural context of the African continent.